The Role of the Nurse Lecturer Situated within a Practice–Education Partnership - Leigh, Jacqueline (International Journal of Practice-based Learning in Health and Social Care, 2016)
Aims and Objectives: To critically explore the nurse lecturers role situated within a practice–education partnership and to identify practice recommendations to operate the role within the context of a partnership in the future. Background: Practice–education partnerships are increasing being developed to operationalize the healthcare policy that advocates partnership working between Academic Education Institutions and healthcare organizations to educate and train the nurse workforce and to develop nursing. A weakness of the reported partnerships is the lack of evidence of how and which partnership processes enable the nurse lecturer to work in a practice role that effectively contributes towards the aims of the partnership and best promotes the practice based learning. Research Design: The single embedded case study is used to evaluate the nurse lecturer’s role from the perspectives of key stakeholders from within an existing practice–education partnership consisting of one School of Nursing and its partner healthcare organizations. Methods: Twenty seven one-to-one interviews and 26 focus groups took place with the range of stakeholders groups at the case study site (i.e. nurse lecturer, professional lead, practice education facilitator, student and education manager). Results: Four key themes emerged: 1. Drivers for the partnership and role of the nurse lecturer. 2. The gap between current role performed and stakeholder role expectations. 3. Academic in Practice (AiP) role conformity: Interplay of three valuing systems. 4. Leadership to drive the partnership. Conclusion: Embedding the nurse lecturer’s role within the practice–education partnership provides a promising approach to sustain a role that best supports practice based learning. Emergent best practice principles for partnership working include: utilising the aims of the partnership as the catalyst to negotiate the practice role performed; and promoting the development of relationships, strong leadership skills and communication as the vehicle to bridge the gap between the current purpose of the role and any future role expectations between key stakeholders. Use of strategies to contest the traditional expectations of the role is needed to promote role creativity and flexibility to enhance the practice based learning.